Numerical study on the behavior and design of a novel multistage hydrogen pressure-reducing valve. (15th April 2022) - Zhang, Yanhong; Liu, Bin; She, Xiaohui; Luo, Yong; Sun, Qiaoyang; Teng, Lin
Abstract: Applying hydrogen fuel-cell vehicles (HFCVs) is feasible to achieve net zero carbon emission in transportation sector. The energy density requirements of these vehicles are fulfilled via high-pressure gaseous hydrogen storage; therefore, an effective pressure-reducing system is necessary. In this work, a novel multistage pressure-reducing valve (named as T–M valve) combining a sleeve pressure structure valve and a Tesla-type orifice valve is proposed. A computational fluid dynamics (CFD) model is developed to analyze the influence of operating parameters on pressure and velocity distributions. Results show that the large pressure and velocity gradients' region is concentrated on the throttling elements. The valve opening and pressure ratio significantly affect energy consumption. In addition, the Mach number in the valve less than one is proposed. This study is conducive to further energy conservation and emission reduction and the research of multistage flow pressure-reducing devices. Highlights: A novel multistage hydrogen pressure-reducing valve using a sleeve pressure structure and Tesla-type orifice valves. Analyze the novel valve behavior using a computational fluid dynamics model. Large pressure and velocity gradients area is concentrated on the throttling elements. The valve opening and pressure ratio significantly affect energy consumption.